EDUKASI PENGOLAHAN SAMPAH PLASTIK RUMAH TANGGA MENJADI PAVING BLOK KEPADA KARANG TARUNA DESA PENGUJAN KECAMATAN TELUK BINTAN TAHUN 2024 - Erpina Santi Meliana Nadeak; Veronika Amelia Simbolon (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Pengujan Village is a coastal area located in Bintan Regency, where the livelihoods and food sources of the community are largely derived from the sea. The increasing activities in fishing and seafood processing have led to the negative impact of rising household waste. The purpose of this community service is to educate the Pengujan Village youth organization (karang taruna) on waste segregation and the processing of household plastic waste into paving blocks. The methods used in this activity include preparation, implementation, and evaluation. Data were analyzed using the paired sample T-test. The results show a significant difference in knowledge before and after the education, with a p-value of 0.014 (α < 0.05). This education is a concrete step to enhance the community's knowledge in waste segregation and the processing of household plastic waste into paving blocks that have economic value.